Assessment of hydrogen gas turbine-fuel cell powerplant for rotorcraft - Baena Mejıas, Rafael; Saias, Chana Anna; Roumeliotis, Ioannis; Pachidis, Vassilios; Bacic, Marko (Elsevier, 2024)
Conventional turboshaft engines are high power density movers suffering from low efficiency at part power operation and producing significant emissions. This paper presents a design exploration and feasibility assessment of a hybrid hydrogen-fueled powerplant for Urban Air Mobility (UAM) rotorcraft. A multi-disciplinary approach is devised comprising models for rotorcraft performance, tank and subsystems sizing and engine performance. The respective trade-offs between payload-range and mission level performance are quantified for kerosene-fueled and hybrid hydrogen tilt-rotor variants. The effects of gas turbine scaling and fuel cell pressurization are evaluated for different hybridization degrees. Gas turbine scaling with hybridization (towards the fuel cell) results in up to 21% benefit in energy consumption relative to the non-scaled case with the benefits being more pronounced at high hybridization degrees. Pressurizing the fuel cell has shown significant potential as cell efficiency can increase up to 10% when pressurized to 6 bar which translates to a 6% increase in overall efficiency. The results indicate that current fuel cells (1 kW/kg) combined with current hydrogen tank technology severely limit the payload-range capability of the tilt-rotor. However, for advanced fuel cell technology (2.5 kW/kg) and low ranges, hybrid powerplant show the potential to reduce energy consumption and reduce emissions footprint.
Keywords: Hybrid propulsion; VTOL; Hydrogen; Fuel cells; UAM